DESA WISATA BERKELANJUTAN DI NGLANGGERAN: SEBUAH TAKTIK INOVASI - Ihsan Rahmat; Ashadi Cahyadi (Jurnal Pariwisata Pesona, 2019)
Innovation important to achieve sustainable organization. Innovation studies in the tourism sector not yet found a reliable theoretical framework and work system. As a result, 8 Tourism Villages in Gunung Kidul Regency threatened to fail. Desa Wisata Nglanggeran (DWN) is claimed to be growing rapidly due to continuous innovation. This study understands the innovation process in DWN using qualitative methods with the Live-in Program as the case. We adopted the innovation framework as a reference for analyzing field findings. The finding is the workings of the DWN community innovation starting from initiation: formulation of the problem, idea generation, and promotion of ideas. Then the development phase is the development of work concepts. Last phase of execution: marketing and post marketing evaluation. The innovation process can work because driven by many factors: involving many actors, having a solid team, oriented to the needs of tourists, building informal communication, and getting community support. The low competence of human resources, unpreparedness, and risk management are the main obstacles. Implications for the rural tourism innovation literature gets community innovation has a relatively similar working with service innovation. The mobilizing the role of key actors and community support is a typical finding this study. We recommended the importance of developing innovation competencies in tourist villages, linking new access to knowledge, and providing special funds.